International Seminar on Environment and Society “Current Challenges and Pathways to Change”, University of Lisbon, Portugal, March 2–3, 2020 - Daria Lebedeva (Journal of Economic Sociology, 2020)
The first International Seminar on Environment and Society was held from March 2nd to 3rd, 2020 in Lisbon, Portugal under the motto of “Current Challenges and Pathways to Change.” The seminar was organized by the Environment and Society Section of the Portuguese Association of Sociology in collaboration with the Institute of Social Sciences of the University of Lisbon and the PhD program in Climate Change and Sustainable Development Policies. The seminar aimed to engage social science researchers in a discussion of global environmental agendas, thus establishing complicated relationships between environment and society (both natural and anthropogenic), their consequences for sustainable development, and critical assessment of the current and forthcoming risks of decision-making for the future. The program was organized in two days: the main sections were held simultaneously in five auditoriums, and the presentations of keynote speakers opened and closed each day. Apart from researchers in sociology and social sciences, the seminar was attended by a wide range of participants from a variety of disciplines including geology, philosophy, and legal studies, representing 19 countries around the world. The keynote speakers of the conference were Alan Irwin (Professor, Copenhagen Business School, Denmark), Luísa Schmidt (Professor, Institute of Social Sciences, University of Lisbon, Portugal), Matthias Gross (Professor, Helmholtz Centre for Environmental Research — UFZ and University of Jena, Germany), Noel Castree (Professor, School of Environment, Education and Development, University of Manchester, United Kingdom). They shared their understandings of the relationships between social groups and the environment and the environment and society as a whole. This seminar has established itself as a crucial event for productive discussion, demonstrating that social scientists around the world are responsive to environmental issues and stand ready to contribute to solving them.